2019
DOI: 10.1016/j.ebiom.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism is a key factor for the persistent spontaneous elite control of HIV-1 infection

Abstract: Background Approximately 25% of elite controllers (ECs) lose their virological control by mechanisms that are only partially known. Recently, immunovirological and proteomic factors have been associated to the loss of spontaneous control. Our aim was to perform a metabolomic approach to identify the underlying mechanistic pathways and potential biomarkers associated with this loss of control. Methods Plasma samples from EC who spontaneously lost virological control (Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 73 publications
3
50
0
Order By: Relevance
“…While no studies have evaluated the impact of plasma metabolic alterations in ATI, one study observed a glycolytic plasma pro le in transient HIV elite controllers (TECs) compared to persistent elite controllers (PECs). 51 Moreover, glutamic acid was shown to be elevated in PECs compared to TECs, 51 corresponding to our observation that glutamate metabolism associated with delayed time to HIV rebound. In totality, a global Warburg phenotype has now emerged as a classic manifestation of HIV infection.…”
Section: Discussionsupporting
confidence: 65%
“…While no studies have evaluated the impact of plasma metabolic alterations in ATI, one study observed a glycolytic plasma pro le in transient HIV elite controllers (TECs) compared to persistent elite controllers (PECs). 51 Moreover, glutamic acid was shown to be elevated in PECs compared to TECs, 51 corresponding to our observation that glutamate metabolism associated with delayed time to HIV rebound. In totality, a global Warburg phenotype has now emerged as a classic manifestation of HIV infection.…”
Section: Discussionsupporting
confidence: 65%
“…Our finding is consistent with a recent study, where spontaneous loss of virologic control and transition from EC status was associated with increased oxidative stress and deregulated mitochondrial function prior to loss of control. Hence, oxidative stress could also be a potential determinant of EC status ( Tarancon-Diez et al., 2019 ). Oxidative stress might be beneficial for HIV-1 replication, and glutathione deficiency is associated with impaired survival in HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another group found contradictory features of HICs compared with HAART treated subjects, that CD8+ T cells from HICs show lower levels of HIF-1A gene expression and higher of VHL, a counteracting gene of HIF-1 ( 86 ), implying that cells from HICs are less primed for glycolysis and activation. The link between metabolism profile and HIV-1 control is further verified by the longitudinal analysis of transient HICs which observed deregulation of metabolites mainly involved in glycolysis, TCA and amino acid metabolism associated with changed Gag-specific CD8+ T cells response preceding loss of viral control ( 87 ). After metabolic reprogramming through IL-15 treatment, CD8+ T cells from non-controllers displayed increased fatty acid uptake and mitochondrial respiratory capacity together with enhanced HIV-1-suppressing capacity ( 86 ).…”
Section: Mini Reviewmentioning
confidence: 84%